Enhancing Political Participation: A Comparative Study of Political Systems in China and Malaysia - Al Giffari, Haekal Adha; Aziz, Nik Muhammad Azimuddin bin; Syifa, Syafitri; Johari, Muhammad Syahzan bin (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
This article compares the political systems of China and Malaysia, focusing on political participation enhancement. It seeks to identify the strengths and weaknesses of their political systems and propose appropriate approaches to enhance political participation in both countries. By examining the structure of government and the effectiveness of political participation, this study expands the current understanding of these political systems in China and Malaysia. It also explores the factors that influence political participation in China and Malaysia. The study finds that political participation in Malaysia is more democratic than in China, considering factors such as party diversity, the electoral process, and the role of local government in accommodating minority voices. However, China's political system demonstrates strength through its centralized control, allowing for the efficient execution of policies and regulations. The study acknowledges similarities between the two countries in terms of their three branches of government but also highlights differences in the type of politically unengaged communities. The findings from this research can be considered by the governments of both countries to improve political participation, particularly among the younger generation. This article, therefore, contributes to the studies on political systems in Asian countries from a comparative perspective.